(3*X)+7=(X*4)+5

Simple and best practice solution for (3*X)+7=(X*4)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3*X)+7=(X*4)+5 equation:


Simplifying
(3X) + 7 = (X * 4) + 5

Reorder the terms:
7 + (3X) = (X * 4) + 5

Reorder the terms for easier multiplication:
7 + (3X) = (4X) + 5

Reorder the terms:
7 + (3X) = 5 + (4X)

Solving
7 + (3X) = 5 + (4X)

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '(-4X)' to each side of the equation.
7 + (3X) + (-4X) = 5 + (4X) + (-4X)

Combine like terms: (3X) + (-4X) = -1X
7 + -1X = 5 + (4X) + (-4X)

Combine like terms: (4X) + (-4X) = 0
7 + -1X = 5 + 0
7 + -1X = 5

Add '-7' to each side of the equation.
7 + -7 + -1X = 5 + -7

Combine like terms: 7 + -7 = 0
0 + -1X = 5 + -7
-1X = 5 + -7

Combine like terms: 5 + -7 = -2
-1X = -2

Divide each side by '-1'.
X = 2

Simplifying
X = 2

See similar equations:

| 4(2p+3)=3+8(p-8) | | 24x^2+41x+12=0 | | -3(1-4k)=3(-1+7k)-5k | | 24x^2+41y+12=0 | | 7b^2-14b-55=0 | | -3(-5n+1)=3(6n-8) | | 9=7p-5p+7 | | y^2=10-6x^2 | | 9x-4=3x-16 | | 3x+5+6x-2=39 | | 4x^3-9x^2+6x=0 | | -2n=3n | | 5n-10=0 | | 40r+48s= | | 9r^2-49=0 | | -6(8+4n)+5(1+4n)=-11 | | 5(b-4)=12 | | -6(8+4n)+5(1+4n)=-1 | | p+.33p=.67 | | 41*8.98= | | 2r^2+7r^2-2r^2= | | x^2-x-14=3x-2 | | 3x+34-x+3=1 | | 8(5k-4)+3(-8k-6)=30 | | 2x^2+16x+42=0 | | 7(2-x)=5x | | 4x^7-20x^6+8x^5=0 | | 8(y-2)+6=2(y+1) | | x^2+6x+13=5 | | 3(2x-4)=3 | | 3w^2+12w+30=0 | | 12(7c+2)= |

Equations solver categories